Integrity Of OKRS And KPIS In Corporate Performance Appraisal System In Jakarta - Bambang Nurakhim; Indri Astuti; Rokhmad Slamet; Haspul Naser (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The use of Integrity Key Performance Indicators (KPIs), Objectives and Key Results (OKRs) is of paramount importance within the context of a performance appraisal system. Both were employed as a means of evaluating employee performance in relation to pre-established objectives. The objective: is to investigate and analyse the impact of OKRs and KPIs on employee rewards in performance appraisal, and to evaluate the importance of maintaining integrity in the performance appraisal system. The research method: employed was as follows: A mixed-methods approach was employed, with qualitative data collected through interviews and quantitative data collected by administering questionnaires to employees in various companies. A total of 112 participants from different institutions were included in the study. The findings of this study: to provide organisations with a roadmap for strengthening the integrity and impact of their performance management systems. The conclusion of this study: is that there are three key areas for improvement: aligning OKRs/KPIs to rewards, implementing transparent feedback loops, and equipping managers to cultivate a fair, motivating appraisal process that enhances employee satisfaction and organisational outcomes.